Traditional milk processing in Borana pastoral area, southern Ethiopia: Practices, food safety, nutrition, and future pathways - Amenu, Kebede; Amdihun, K. (CAB International, 2025)
This study was designed to explore traditional milk handling practices and the perceived role of the practice on the quality of traditional fermented milk. Data were collected through in-depth interviews and focus group discussions. In the study area, fresh milk is stored in a smoked, traditional pear-shaped container called gorfa and left to ferment naturally at ambient temperature. The whey (fluid) part is removed every 2–3 days, and more fresh milk is added into the container continuously. The fermentation process can take 7 days to 3 months, resulting in a product locally called ititu. Fermented milk plays a vital nutritional role in the diet, contributing significantly to food and nutrition security. Apart from natural fermentation, there is no standard culture in the area. Smoking of milk containers using specific woods is widely practised in Borana to sanitise the containers. Smoking of milk utensils is perceived to assure the quality and safety of milk and dairy products. However, because of the absence of standardised hygiene practices, smoking alone may not guarantee the safety of the product. Integrating basic food safety principles with indigenous knowledge can improve the microbiological quality of milk products.